1902 Ga. Laws 434-35 - (:unkn) unknown (My University, 1902)
§ 16: Granted the mayor and alderman the authority to license, regulate, and control by ordinance all gun shops, dealers in guns, or pistols.
Keywords: LICENSE - DEALERS